2018
DOI: 10.19102/icrm.2018.091106
|View full text |Cite
|
Sign up to set email alerts
|

An “UninTENSional” Subcutaneous Implantable Cardioverter-defibrillator Shock

Abstract: Subcutaneous implantable cardioverter-defibrillators (ICDs) (S-ICDs) are advantageous because they eliminate the need for transvenous leads. However, just like in the case of traditional ICDs, inappropriate shocks are an unwanted complication that may result following their placement. In this case, we discuss the mechanism of an inappropriate shock in a patient with an S-ICD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In contrast to DBS and SCS, there are more reported adverse interactions between CIED and TENS units. Both Singh et al [ 14 ] and Shenoy et al [ 15 ] reported EMI from a TENS unit that resulted in an ICD shock. Singh et al [ 14 ] details a S-ICD shock after a patient underwent TENS therapy in the neck, axilla, and back.…”
Section: Cied Response To Internal and External Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to DBS and SCS, there are more reported adverse interactions between CIED and TENS units. Both Singh et al [ 14 ] and Shenoy et al [ 15 ] reported EMI from a TENS unit that resulted in an ICD shock. Singh et al [ 14 ] details a S-ICD shock after a patient underwent TENS therapy in the neck, axilla, and back.…”
Section: Cied Response To Internal and External Devicesmentioning
confidence: 99%
“…Both Singh et al [ 14 ] and Shenoy et al [ 15 ] reported EMI from a TENS unit that resulted in an ICD shock. Singh et al [ 14 ] details a S-ICD shock after a patient underwent TENS therapy in the neck, axilla, and back. This adverse interaction was likely due to the relatively superficial location of the S-ICD and its increased susceptibility to EMI, which ultimately led to an ICD shock after the device detected low-amplitude and high frequency signals[ 14 ].…”
Section: Cied Response To Internal and External Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is a likely assertation bias because normal functioning devices are unlikely to be reported. In this regard, we only found twenty-two such reports of S-ICD with confirmed lack of EMI and MP in the literature [9,10,14,15,[18][19][20][21]25,27,[28][29][30][33][34][35][36][37]42,43,47,48]. It is noteworthy that the largest published patient series of S-ICD demonstrated that 0.5% to 8% of patients experienced EMI or MP [7,18].…”
Section: Limitationsmentioning
confidence: 99%